Thymol and Piperine-Loaded Poly(D,L-lactic-co-glycolic acid) Nanoparticles Modulate Inflammatory Mediators and Apoptosis in Murine Macrophages - Dzoyem, Jean Paul; Boulens, Nathalie; Allémann, Eric; Delie, Florence (Planta Medica International Open, 2021)
This study aimed at preparing and characterizing thymol, eugenol, and piperine-loaded poly(D,L-lactic-co-glycolic acid) nanoparticles and evaluating the effect on inflammatory mediators secretion and apoptosis in Raw 264.7 macrophage cells. Nanoparticles were produced by the solvent evaporation technique. Dynamic light scattering and scanning electron microscopy were used to study the physicochemical characteristics. Raw 264.7 macrophage cells were used as a model for in vitro assays. The 2-(4-iodophenyl)-3-(4-nitrophenyl)-5-(2,4-disulfophenyl)-2H-tetrazolium assay was used to determine the cytotoxicity of the formulated nanoparticles. An annexin V apoptosis detection kit was used to assess apoptosis. Nitric oxide production was determined using the Griess reagent, and the inflammatory mediators level was evaluated with Th1/Th2 cytokine and fluorometric cyclooxygenase kits. The loaded nanoparticles showed a particle size around 190 nm with a low polydispersity between 0.069 and 0.104 and a zeta potential between–1.2 and–9.5 mV. Reduced cytotoxicity of nanoparticles compared to free molecules against Raw 264.7 macrophage cells was observed and seemed to occur through a mechanism associated with apoptosis. A decrease in cyclooxygenase enzyme activity with an increasing concentration was observed. Both free molecules and nanoparticles showed their capacity to modulate the inflammatory process mostly by inhibiting the investigated inflammatory cytokines. The data presented in this study indicate that thymol and piperine-loaded poly(D,L-lactic-co-glycolic acid nanoparticles could serve as a novel anti-inflammatory colloidal drug delivery system with reduced toxicity. However, further study should be considered to optimize the formulation’s loading capacity and thereby probably enhance their bioactivity in treating inflammatory diseases.
Keywords: thymol; piperine; nanoparticles; anti-inflammatory activity; cytokines; apoptosis